What is Libra? Understanding Facebook's currency - Maik Schmeling (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
Facebook's proposal to create a global digital currency, Libra, has generated a wide discussion about its potential benefits and drawbacks. This note contributes to this discussion and, first, characterizes similarities and dissimilarities of Libra's building blocks with existing institutions. Second, the note discusses open questions about Libra which arise from this characterization and, third, potential future developments and their policy implications. A central issue is that Libra raises considerable questions about its role in and impact on the international monetary and financial system that should be addressed before policymakers and regulators give Libra the green light.
Keywords: 330